Decreased Cigarette Smoking but No Change in Use of Electronic Cigarettes Following a University-Wide Smoking Ban. (September 2019) - Allen, Ben; Stuart, Gregory L.
The prevalence of electronic cigarette use is increasing, particularly among youth. This recent trend is troubling given that electronic cigarette use is associated with future cigarette smoking. Here, we assessed the prevalence of cigarette smoking and use of electronic cigarettes among college students before and after implementation of a university-wide smoking ban on campus. We found that after the smoking ban was implemented, the prevalence of self-reported combustible cigarette smoking decreased (12% versus 7%; unadjusted: OR = 0.55, 95% CI = 0.34, 0.89, p = 0.015), but we did not observe a difference in the prevalence of electronic cigarette use (26.3% versus 27.5%; unadjusted: OR = 1.06, 95% CI = 0.78, 1.43, p = 0.699). Future studies should identify factors that increase the impact of university smoking policies on electronic cigarette use.